2016
DOI: 10.1186/s12916-016-0561-2
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of competencies for scientific editors of biomedical journals

Abstract: BackgroundBiomedical journals are the main route for disseminating the results of health-related research. Despite this, their editors operate largely without formal training or certification. To our knowledge, no body of literature systematically identifying core competencies for scientific editors of biomedical journals exists. Therefore, we aimed to conduct a scoping review to determine what is known on the competency requirements for scientific editors of biomedical journals.MethodsWe searched the MEDLINE®… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 14 publications
0
40
0
1
Order By: Relevance
“…Subsequently, in line with Galipeau and colleagues 22 , after this initial categorization, we collated overlapping or duplicate categories into themes. Then, two reviewers (KDC, AG) evaluated recurring themes in the work to synthesize the data.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, in line with Galipeau and colleagues 22 , after this initial categorization, we collated overlapping or duplicate categories into themes. Then, two reviewers (KDC, AG) evaluated recurring themes in the work to synthesize the data.…”
Section: Methodsmentioning
confidence: 99%
“…Since editors perform their duties largely without any formal training (Galipeau et al 2016), this would require at least some education about publication paradigms, dogmas and power distributions as part of existing work directed towards publication ethics. At the very least, editors should be made aware that they are operating within a number of paradigms, some with respect to the epistemic content of their discipline and journal, some with respect to publishing practices.…”
Section: Recommendationsmentioning
confidence: 99%
“…Readers have the right to expect that they do their utmost best to implement all reasonable standards to ensure the quality of the articles that are published in the journal. Interestingly, not much evidence is available what competencies editors should have to meet these standards . Through a scoping review competencies for editors were identified and these were then developed further through a modified Delphi procedure for which editors through major editorial organizations such as the World Association of Medical Editors (WAME) and Committee on Publication Ethics (COPE) were invited.…”
mentioning
confidence: 99%
“…Interestingly, not much evidence is available what competencies editors should have to meet these standards . Through a scoping review competencies for editors were identified and these were then developed further through a modified Delphi procedure for which editors through major editorial organizations such as the World Association of Medical Editors (WAME) and Committee on Publication Ethics (COPE) were invited. This resulted in a list of 23 competency‐related statements for which >90% consensus existed .…”
mentioning
confidence: 99%